Analysis of Nurse Work Stress Factors During the COVID-19 Pandemic - Umi Fatikhatul Luthfiyah; Chriswardani Suryawati; Antono Suryoputro (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Based on the preliminary study at Prof dr. Soekandar Hospital, it was found that out of 30 nurses, 50% of them found it often difficult to relax and feel tired often. In addition, the results show that 76.90% of them feel very drained of energy. This study aimed to determine the relationship between personal and organizational factors and the occurrence of work stress for nurses during the COVID-19 pandemic at Prof. dr. Soekandar Hospital. This research was a quantitative observational study using a cross-sectional study design. The number of samples in this study amounted to 145 respondents using a purposive sampling technique. Data analysis used the Pearson test and linear regression. The events of work stress for nurses were unaffected by work shifts. The variables that affect the incidence of work stress are social support, workload, work shift, and the policies on the use of PPE. Based on the results of the multivariate test, 41.2% of nurses’ work stress was influenced by social support, workload, work shifts, and policies on the use of PPE. Variables that simultaneously affect the incidence of work stress for nurses are workload and nurses’ work shifts.